Revealing the Tree Species Diversity within Koto Mahligai Temple Ruin, Muaro Jambi - Rizmoon Nurul Zulkarnaen; Muhammad Rifqi Hariri; Lutfi Rahmaningtyas; Wahyu Adi Nugroho (Jurnal Sylva Lestari, 2023)
Koto Mahligai Temple is a cultural heritage site in the Muaro Jambi Regency. Environmental disturbances, especially plant-related ones, are rare at this precious shrine. As a result, plant diversity is still sustained. The research aimed to evaluate the plant diversity and general vegetation condition in the Koto Mahligai Temple. The method used was the comprehensive inventory approach, focusing on woody plants through the census sampling method. Vital data were meticulously collected for each tree, including height, diameter, and morphological characteristics. The result found 246 trees from 26 species in the vicinity, including native and introduced species. Local plants that are infrequently seen in urban areas, such as Bouea macrophylla, Canthiumera robusta, Dillenia sumatrana, Flacourtia rukam, and Semecarpus heterophyllus, are among these species. The result suggested that the Koto Mahligai Temple could be well developed into a public site for stakeholders interested in studying plant diversity in Muaro Jambi Regency, owing to the variety and distinctiveness of its plants. Furthermore, the cultural significance of these plants is tied to the Koto Mahligai Temple, which attracts tourists. The study emphasizes the need for future strategies that harmonize plant preservation, archaeological exploration, and temple restoration efforts. Keywords: diversity, enigmatic species, Koto Mahligai, native plant, Sumatra